Genome-based reclassification of Bacillus okuhidensis as a later heterotypic synonym of Bacillus halodurans. Issue 11 (22nd August 2019) - Liu, Guo-Hong; Narsing Rao, Manik Prabhu; Dong, Zhou-Yan; Wang, Jie-Ping; Che, Jian-Mei; Chen, Qian-Qian; Sengonca, Cetin; Liu, Bo; Li, Wen-Jun
Abstract : The present study was carried out to clarify the taxonomic relationship between two closely related Bacillus species, Bacillus okuhidensis Li et al . 2002 and Bacillus halodurans (ex Boyer 1973) Nielsen et al. 1995. The maximum-likelihood tree based on the 16S rRNA gene sequence and the phylogenomic tree based on concatenation of 16 protein-marker genes showed that these species were similar. Average nucleotide identity (ANIm 99.25 %, ANIb 98.2 %) and digital DNA–DNA hybridization values (93.5 %) between B. okuhidensis DSM 13666 T and B. halodurans DSM 497 T were greater than the threshold values for bacterial species delineation, indicating that they belong to the same species. Therefore, B. okuhidensis Li et al. 2002 should be reclassified as a later heterotypic synonym of B. halodurans (ex Boyer 1973) Nielsen et al. 1995.